Оксиданти и антиоксиданти у инфаркту миокарда (МИ); Испитивање албумина модификованог исхемијом, малондиалдехида, супероксид дисмутазе и каталазе код особа којима је дијагностикован СТ са повишеним инфарктом миокарда (СТЕМИ) и који нису СТЕМИ (НСТЕМИ): Oxidative Stress and Antioxidant status in ACS. - Aladağ, Nesim; Asoğlu, Ramazan; Özdemir, Mahmut; Asoğlu, Emin; Atabey, Rukiye Derin; Demir, Canan; Demir, Halit (Journal of Medical Biochemistry, 2020)
Background: Coronary ischemia can lead to myocardial damage and necrosis. The pathogenesis of cardiovascular diseases often includes increased oxidative stress and decreased antioxidant defense. The study aimed to assess levels of ischemia modified albumin (IMA), malondialdehyde acid (MDA), superoxide dismutase (SOD), and catalase in individuals diagnosed with ST elevated myocardial infarction (STEMI) and non-STEMI.Methods: The present study prospectively included 50 STEMI patients, 55 NSTEMI patients, and 55 healthy subjects. Only patients who were recently diagnosed with STEMI or NSTEMI were included in this study. IMA, MDA, SOD, and catalase activities were measured spectrophotometrically. Significant coronary artery lesions were determined by angiography.Results: Patients with ACS had significantly greater IMA and MDA values than the healthy controls (p